AMONGST THE BIG WORLD AND THE CASA: THE PASSAGE THROUGH SOCIAL AND EDUCATIONAL CARE CENTRE FOR ADOLESCENTS - CASA FOUNDATION AND THE APPROACH TO PRISON SYSTEM CODES - GONÇALVES, Rosângela Teixeira (Faculdade de Filosofia e Ciências, 2015)
Analyzes the profile, the trajectory and the representations of young egress of social and educational units of the CASA Foundation concerning the compliance period of the detention procedure and social and educational measures in an open environment of assisted liberty. As conclusions, the research highlights that for the seven interviewed young people, egresses of the CASA Foundation units, inpatient social and educational measures is being understood as penalty and social and educational units, as prison. In the first passage, young people spend incorporate into your vocabulary a native language of penitentiaries to refer to by its illegal acts, to comply with the measure to differentiate the institution of the big world and avail himself of the rules and procedures the First Command of Capital. Thus when at liberty, the social and educational measure of inpatient enlarges the positive status of young egress facing the crime and the negative status front of the school institution and the world of work. Submissão: 2015-08-17 Aceite: 2015-10-20